2020
DOI: 10.1016/j.ssc.2019.113767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten on the vacancy behaviors in Ta–W alloys from first-principles calculations

Abstract: Alloying elements play an important role in the design of plasma facing materials with good comprehensive properties. Based on first-principles calculations, the stability of alloying element W and its interaction with vacancy defects in Ta-W alloys are studied. The results show that W tends to distribute dispersedly in Ta lattice, and is not likely to form precipitation even with the coexistence of vacancy. The aggregation behaviors of W and vacancy can be affected by their concentration competition. The incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The analysis shows that these Ti-Vac structures contain up to 16 vacancies, although the minimum distance between vacancies is larger than or equal to the bcc lattice constant (2nd coordination sphere), preventing void formation. Recently, Lv et al [27] reported a similar effect in the Ta-W alloy, where W atoms suppress the aggregation of vacancy defects. The formation of Ti-Vac complexes aligns with the results from a positron annihilation study of a V-5Ti alloy, where no micropores were found except for monovacancies [28].…”
Section: Tablementioning
confidence: 81%
“…The analysis shows that these Ti-Vac structures contain up to 16 vacancies, although the minimum distance between vacancies is larger than or equal to the bcc lattice constant (2nd coordination sphere), preventing void formation. Recently, Lv et al [27] reported a similar effect in the Ta-W alloy, where W atoms suppress the aggregation of vacancy defects. The formation of Ti-Vac complexes aligns with the results from a positron annihilation study of a V-5Ti alloy, where no micropores were found except for monovacancies [28].…”
Section: Tablementioning
confidence: 81%
“…Tungsten has the advantages of a high melting point, high thermal conductivity and low sputtering rate [4], and it has been identified as a divertor material for ITER, as well as being considered one of the most promising candidate plasma-facing materials (PFMs) for future fusion reactors [5,6]. However, as a metal with a body-centered cubic (BCC) structure and because of its electronic structure, characteristics of inter atomic bonds and lattice resistance of dislocation stress field, pure tungsten materials have inherent brittleness at lower temperatures (high ductile-to-brittle transition temperature, DBTT) [7,8], brittleness caused by recrystallization [9] and neutron irradiation when used as PFMs [10]. In the past, researchers prepared various new tungsten-based materials with significantly improved mechanical properties through doping [11], alloying [12,13] or microstructural modification methods [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ta-10W has great potential in the aerospace and nuclear industries due to its good formability, high melting point, excellent high-temperature strength and corrosion resistance (Byun and Maloy, 2008;Liu et al, 2018;Li et al, 2020;Lv et al, 2020). It has attracted considerable attention for high-temperature structural components in aerospace and the jacket for nuclear waste (Zhou et al, 2015;Novakowski et al, 2018;Wang et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%